Peran Media Massa Inggris dan Jerman dalam Menginformasikan Pandemi COVID-19 - Rizky Anggraini; Henny Saptatia (Jurnal Riset Komunikasi, 2021)
The emergence of the Covid-19 pandemic in various parts of the world has provided speculation and news that takes care of public spaces including Mass Media in Britain and Germany. The role of the Internet and the mainstream press media cannot answer in terms of disseminating information about COVID-19 to the public. This research examines how the British and German Mass Media reported the spread of COVID-19 and about how the mass media played a role in reporting on the health crisis that occurred in the two countries. The object of research chosen was the online news platform in the form of British and German mainstream media, each of which had a different character. This study aims to understand the role of the media in coverage of the COVID-19 pandemic health crisis, the theory used in this study is the framework and theory of social media responsibility. So it can be seen to what extent the media has played a role in providing information about the health crisis that occurred in the two countries.